Genetic resistance to gastrointestinal nematode parasites in some indigenous breeds of sheep and goats in East Africa - Baker, R.L.; Rege, J.E.O.; Tembely, S.; Mukasa-Mugerwa, E.; Anindo, D.O.; Mwamachi, D.M.; Thorpe, W.R.; Lahlou-Kassi, A. (ICWCGALP, 1998)
Research in Kenya has confirmed that Red Maasai sheep are more resistant to gastrointestinal parasites than Dorper sheep and has shown that Small East African goats are more resistant than Galla goats. There is no difference in resistance between the Menz and Horro sheep breeds in Ethiopia. Heritability estimates in 8 month old lambs in Kenya were 0.18 (+ or -) .08 for logarithm transformed faecal egg counts (FEC), but higher in the susceptible Dorper-sired lambs (0.35 (+ or -) .16) than in the resistant Red Maasai-sired lambs (0.06 (+ or -) .07). In Ethiopia the heritability for log FEC in 3-month-old lambs at weaning was 0.14 (+ or -) .05, with a lower heritability in the better adapted Menz lambs (0.09 (+ or -) .05) than in the Horro lambs (0.23 (+ or -) .09).